2021
DOI: 10.1002/ecs2.3551
|View full text |Cite
|
Sign up to set email alerts
|

Reversing tree expansion in sagebrush steppe yields population‐level benefit for imperiled grouse

Abstract: Woody plant expansion into shrub and grasslands is a global and vexing ecological problem.In the Great Basin of North America, the expansion of pinyon-juniper (Pinus spp.-Juniperus spp.) woodlands is threatening the sagebrush (Artemisia spp.) biome. The Greater Sage-grouse (Centrocercus urophasianus; sage-grouse), a sagebrush obligate species, is widespread in the Great Basin and considered an indicator for the condition of sagebrush ecosystems. To assess the population response of sage-grouse to landscape-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
3
29
0
Order By: Relevance
“…The continued decline in λ since 2016 suggested the loss of 186,972 ha of sagebrush habitat and slow regeneration of sagebrush plants post‐fire may prolong recovery of sage‐grouse after a mega‐wildfire (Steenvoorden et al, 2019). Mean estimates of λ during 2016–2018 were much lower in the Trout Creek study area (0.75) compared to a study in Oregon during the same time period that was not affected by fire (0.93; Olsen et al, 2021). Moreover, estimates of λ were low compared to other studies that reported long‐term trends in λ across the distribution of sage‐grouse (Dahlgren et al, 2016; Garton et al, 2011; Johnson & Braun, 1999).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The continued decline in λ since 2016 suggested the loss of 186,972 ha of sagebrush habitat and slow regeneration of sagebrush plants post‐fire may prolong recovery of sage‐grouse after a mega‐wildfire (Steenvoorden et al, 2019). Mean estimates of λ during 2016–2018 were much lower in the Trout Creek study area (0.75) compared to a study in Oregon during the same time period that was not affected by fire (0.93; Olsen et al, 2021). Moreover, estimates of λ were low compared to other studies that reported long‐term trends in λ across the distribution of sage‐grouse (Dahlgren et al, 2016; Garton et al, 2011; Johnson & Braun, 1999).…”
Section: Discussionmentioning
confidence: 63%
“…Vital rates most important for driving sage‐grouse population change ( λ ) can vary among populations (e.g., Walker & Naugle, 2011 vs. Dahlgren et al, 2016). For example, several studies have reported λ to be most sensitive to changes in adult female survival, juvenile (fledging to 1‐year old) survival, and chick survival (Dahlgren et al, 2016; Johnson & Braun, 1999; Olsen et al, 2021; Taylor et al, 2012). However, nest success explained most of the variation in λ across multiple populations representing the current sage‐grouse distribution, in part due to the high temporal variation in this vital rate (Taylor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis in our study area indicated annual female survival increased 6.6% and nest survival increased 18.8% in the Treatment relative to the Control during the first 3 years after conifer removals were initiated (Severson et al 2017d). A longer-term assessment of demographic consequences of conifer removal indicated an 11-13% increase in population growth rate (λ) in the Treatment relative to the Control 5-6 years after conifer removals began (Olsen et al 2021). Conifer expansion may increase perch sites for avian predators of sagegrouse (Paton 1994, Wolff et al 1999) and contribute to environments with higher risk of mortality, even when trees are sparse and scattered (Coates et al 2017, Prochazka et al 2017).…”
Section: Discussionmentioning
confidence: 70%
“…Positive effects of conifer removal on habitat availability for sage-grouse may also result in demographic benefits (Sandford et al 2017, Severson et al 2017d, Olsen et al 2021. Sage-grouse broods in Utah were more likely to be successful (≥1 chick surviving ≥50 days) when occupying habitat at lower conifer levels and closer to conifer removal areas (Sandford et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation